2017
DOI: 10.1002/bdm.2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Effort: Influences of Evaluation Mode on Judgments of Task‐specific Efforts

Abstract: The claim that humans adapt their actions in ways that avoid effortful processing (whether cognitive or physical) is a staple of various theories of human behavior. Although much work has been carried out focusing on the determinants of such behaviors, less attention has been given to how individuals evaluate effort. In the current set of experiments, we utilized the general evaluability theory to examine the evaluability of effort by examining subjective value functions across different evaluation modes. Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 109 publications
(167 reference statements)
0
15
0
Order By: Relevance
“…That is, the qualitative change between “not rotated” and “rotated” might weigh heavily when individuals are inferring effort based on beliefs and are relatively separated from the experience of processing the stimulus. The idea that, in certain situations, incremental differences are less salient than are categorical differences has been suggested previously ( Dunn et al, 2017 ; Hsee & Zhang, 2010 ). Critically, reading times reveal relatively modest effects for certain stimulus rotations (e.g., UW-UF vs. UW-RF).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…That is, the qualitative change between “not rotated” and “rotated” might weigh heavily when individuals are inferring effort based on beliefs and are relatively separated from the experience of processing the stimulus. The idea that, in certain situations, incremental differences are less salient than are categorical differences has been suggested previously ( Dunn et al, 2017 ; Hsee & Zhang, 2010 ). Critically, reading times reveal relatively modest effects for certain stimulus rotations (e.g., UW-UF vs. UW-RF).…”
Section: Discussionmentioning
confidence: 91%
“…The critical contribution was the discovery of a stimulus type by judgement type interaction in the context of judgements of effort, which could be interpreted as a shift in the sources of information used to inform judgements of effort as a function of judgement type. Future work aiming to illuminate the underlying factors that contribute to judgements of effort, along with focusing on the effects of various contexts (e.g., single vs. joint evaluation; Dunn et al, 2017 ) in which judgements of effort are made, will provide a deeper understanding of decisions about our expenditures of cognitive effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common code hypothesis also predicts that other aspects of a task, like energy expenditure, time, utility, and consequence of mistakes, should be convertible to the perceived difficulty and hence be systematically comparable. Given that different demands have different levels of evaluability (Dunn et al, 2017), further experiments are needed to better understand how different demands are compared. We did not explore all of these potential contributors to perceived difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a single evaluation mode, some reference information is required to allow choices. Dunn et al ( 2017 ) investigated the evaluability of stimulus rotation, set size, and weight. Stimulus rotation appeared as a not evaluable feature and the authors suggested that error or failure knowledge might be required to make a feature evaluable.…”
Section: Discussionmentioning
confidence: 99%